Designing Accounting Information Systems for Primary Cash Receipts and Expenditures in Open ERP-based Retail Units (ODOO) - Putri Navalina, Ivana Larasati; Ludfi Djajanto; Ari Kamayanti (HM Publisher, 2021)
Over time, this type of cooperative business slowly begins to lose its existence due to increasingly fierce business competition. This is because the role of cooperatives, which is identical to the provision of basic foodstuffs for the needs of the community, has now been taken over by the existence of supermarkets both in cities and in the regions. This is due to the influence of the industrial technology revolution 4.0 which requires business people to continue to be able to improve services and offer technology-based convenience so that it has an impact on customer satisfaction. This literature review aims to describe the role of the use of information technology systems for accounting for primary cash receipts and disbursements in cooperatives.